Career development, job satisfaction, and career commitment: evidence from the Singaporean hospitality industry - Pearson, Cecil; Ananthram, Subramaniam (Institute of Management Technology, 2008)
Changing aspirations of contemporary employees is compelling employers to facilitate corporate frameworks for enhancing employee retention rates. One scheme to reduce attrition is fostering greater career satisfaction and career commitment through enlightened career path planning. This study reports findings from the analysis of data provided by 505 employees of a leading Singaporean hotel to reveal career path planning and career management, substantial predictors of career development, which was significantly related to career satisfaction and career commitment. It was also found that women and men held similar perspectives for all the assessments, but older employees reported significantly less importance for career planning and career development. Insights for strengthening organization- employee linkages are presented.